Effect of Insecurity on the Performance of Cooperative Thrift and Credit Society (CTCS) Membership in Nnewi North Local Government Area, Anambra State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
This study investigated the effect of insecurity on the performance of Cooperative Thrift and Credit Society (CTCS) members in Nnewi North Local Government Area of Anambra State. The research was motivated by the need to provide empirical evidence on how insecurity influences cooperative activities, as most existing studies have focused on commercial banks while neglecting grassroots financial institutions like CTCS. The research specifically focused on the effect of insecurity on savings behavior of CTCS members, the effect of insecurity on investment decisions and the effect of insecurity on member participation in cooperative activities. The study was guided by the Perceived Risk Theory, which explains how threats and uncertainty influence financial decision-making and collective participation. A descriptive survey research design was adopted, and the study population consisted of 205 CTCS members in Nnewi North. Using Taro Yamane’s formula, a sample was drawn, and structured questionnaires were distributed. Out of these, 160 were duly completed and returned for analysis. Descriptive statistics such as frequency counts, percentages, and mean were used to analyze demographic characteristics and members’ perceptions, while Pearson Product Moment Correlation was employed to test the study hypotheses. The findings revealed that insecurity significantly affects cooperative performance. Strong positive correlations were found between insecurity and savings behavior (r = 0.755), investment decisions (r = 0.722), and members’ participation (r = 0.885), all at a 0.00 level of significance. These results indicate that insecurity discourages consistent savings, reduces members’ willingness to invest, and weakens active participation in cooperative activities. The study concludes that insecurity poses a serious threat to the financial and social sustainability of CTCS in Nnewi North. It recommends stronger risk management strategies, improved collaboration with security agencies such as the Nigeria Police Force, Nigeria Security and Civil Defence Corps, and local vigilante groups operating within Nnewi North communities, as well as confidence-building measures to sustain cooperative operations in insecure environments.
Keywords: Insecurity; Thrift and Savings; Cooperatives; Investment; Member participation